Effect of Different Ratios of Glycerol and Erythritol on Properties of Corn Starch-Based Films - Wang, Bin; Xu, Xin; Fang, Youxin; Yan, Shouxin; Cui, Bo; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
The demand for bio-compatible plastic products has increased; hence, a suitable method for producing green composites is essential. This study prepared corn starch-based films using the solution casting method, and the physicochemical properties of the prepared films were investigated using a mixture of glycerol (GLY) and erythritol (ERY) at different ratios (4:0, 3:1, 2:2, 1:3, and 0:4) as plasticizing agents. The crystallinity, hydrophilicity, and thermal stability of corn starch-based films were analyzed using small-angle X-ray diffraction, an optical contact angle instrument, and a thermal stability analysis instrument. With the increase in GLY ratio, the thickness, water-solubility, water content, water vapor permeability, elongation at break, and V-shaped crystallization of the corn starch-based films increased. The tensile strength and the thermal stability decreased with increasing the GLY ratio. We developed a new plasticizer to improve the properties of starch films and provided a theoretical basis for the industrial production of corn starch-based films.